Prevention and Recovery Care Services in Australia: Describing the Role and Function of Sub-Acute Recovery-Based Residential Mental Health Services in Victoria - Fletcher, Justine; Brophy, Lisa; Killaspy, Helen; Ennals, Priscilla; Hamilton, Bridget; Collister, Laura; Hall, Teresa; Harvey, Carol (Frontiers in Psychiatry, 2019)
Background: Prevention and Recovery Care (PARC) services are relatively new sub-acute residential services that have supported people with mental-ill health in Victoria since 2003. Operated from a partnership model between non-governmental agencies and clinical mental health services, PARC services integrate intensive recovery-focused psychosocial input with clinical mental health care. Aim: to describe and contrast the nineteen PARC services operating in Victoria at the time of the study, in terms of structures and function, resources, and content and quality of care. Method: Nineteen participants, one representing each PARC, completed two surveys: the first, a purpose-designed survey relating to the government guidelines for PARC services and the second, the Quality Indicator for Rehabilitative Care. Results: Descriptive analyses highlighted that PARC services have operated in inner city, urban and regional areas of Victoria, from between one and fourteen years. Participants reported that a recovery approach was at the core of service delivery, with a vast array of group and individual programs on offer. Across the state there was variation in the quality of services according to the Quality Indicator for Rehabilitative Care domains. Conclusions: This study highlights variation in the structure and function, resourcing, content and quality of care offered across the Victorian PARC services, which is inline with Government guidelines that promote a service model which is adaptable to local need. The findings indicate emerging evidence that PARCs are providing recovery-oriented services, that offer consumers autonomy and social inclusion, and therefore likely enabling a positive consumer experience. The range of individual and group programs is in line with the Victorian guidelines, offering practical assistance; therapeutic activities; and socialisation opportunities consistent with consumer preferences.